Design And Implementation Of SSO (Single Sign On) Using Ldap Authentication For Information System And Hotspot Access At Pesma KH Mas Mansur UMS - Riyanto, Agus; , Agus Ulinuha, ST., MT., Ph.D (2014)
PESMA K.H Mas Mansur ums every year, there are a lot of students from many cities and countries who want to stay in the boarding house. Because of the increasing number of students, PESMA should increase the facilities. Internet is very important for staff and students. Staff accesses the internet to manage the data. Student accesses the internet to find and access the information and journal. Single Sign On (SSO) is a system which facilitates a user account for accessing the data in servers. This method is implementation at PESMA KH Mas Mansur UMS which integrate between information system and hotspot. Install and configuration SSO server, configuration router hotspot. Student doesn't need to memorize many usernames and passwords, eases data processing. If each server has user data, then the user data processing (add, delete, edit) should be done in every server. By using SSO, only need one time process. The SSO implementation helps student for using information system and hotspot access with one account login that has been registered and helps administrator to organize data about user who access system. It is caused by the use of LDAP as single user data. Furthermore data is stored centrally in one server. After implementing SSO students need only to memorize one username and password to login to any information system and hotspot access